Implementation of egg incubator control system at La Tansa Firdaus Farm Purwakarta - Diky Zakaria; Ade Gafar Abdullah; Ahmad Fauzi; Galura Muhammad Suranegara; Excel Thrive Valerian Haryanto; Muhammad Raihan Ramadhan; Edgard Altamerano Ferdinand; Rifki Destrizal Nugraha (Universitas Pendidikan Indonesia, 2026)
Chicken farming is a promising business opportunity, as most Indonesians enjoy chicken meat and eggs. This community service program aims to improve the hatching success rate of free-range chicken eggs at La Tansa Firdaus Farm through the implementation of an Internet of Things (IoT)-based Egg Incubator Control System. Partners previously used conventional incubation methods with incandescent lamps, yielding a success rate of only 70-75%. The program was implemented using a Participatory Action Research (PAR) approach through several stages, including problem identification, system design, material development, training, implementation, and monitoring and evaluation. Three modified incubators with automatic temperature control systems and a web-based monitoring dashboard were donated to partners and implemented. In addition to technical training on incubator use, digital marketing training was also provided to improve the competitiveness of livestock products. Evaluation results showed that partners gained increased technical capacity, understood how to operate and maintain the system, and expressed the hope that this technology could increase the hatching success rate to 80-85%. Partners also demonstrated a commitment to implementing and developing the technology sustainably. This program proves that simple IoT-based technological innovations can have a real impact on increasing the productivity of smallholder livestock farming. Abstrak Peternakan ayam merupakan salah satu usaha yang memiliki prospek bagus. Hal ini karena mayoritas masyarakat Indonesia menyukai daging dan telur ayam. Program pengabdian kepada masyarakat ini bertujuan untuk meningkatkan tingkat keberhasilan penetasan telur ayam kampung di La Tansa Firdaus Farm melalui penerapan Egg Incubator Control System berbasis Internet of Things (IoT). Mitra sebelumnya menggunakan metode penetasan konvensional dengan lampu pijar yang hanya menghasilkan tingkat keberhasilan sekitar 70-75%. Kegiatan dilaksanakan dengan pendekatan Participatory Action Research (PAR) melalui beberapa tahapan, meliputi identifikasi masalah, perancangan sistem, penyusunan materi, pelatihan, implementasi, serta monitoring dan evaluasi. Tiga unit inkubator yang telah dimodifikasi dengan sistem kendali suhu otomatis dan dashboard pemantauan berbasis web telah dihibahkan dan diimplementasikan kepada mitra. Selain pelatihan teknis penggunaan inkubator, diberikan pula pelatihan pemasaran digital untuk meningkatkan daya saing produk peternakan. Hasil evaluasi menunjukkan bahwa mitra memperoleh peningkatan kapasitas teknis, memahami cara operasi dan perawatan sistem, serta memiliki harapan bahwa teknologi ini dapat meningkatkan tingkat keberhasilan penetasan menjadi 80-85%. Mitra juga menunjukkan komitmen untuk menerapkan dan mengembangkan teknologi tersebut secara berkelanjutan. Program ini membuktikan bahwa inovasi teknologi sederhana berbasis IoT dapat memberikan dampak nyata terhadap peningkatan produktivitas peternakan rakyat. Kata Kunci: Internet of Things; pemberdayaan masyarakat; sistem pengendalian inkubator telur; sistem penetasan